Glass Transition in Crosslinked Nanocomposite Scaffolds of Gelatin/Chitosan/Hydroxyapatite - Karina N. Catalan (Polymers, 2019)
The development of biopolymeric scaffolds crosslinked with nanoparticles is an emerging field. Gelatin/chitosan scaffolds are gaining interest in medical areas, e.g., bone tissue engineering, given their suitability for nano-hydroxyapatite incorporation. The glass transition temperature is a thermodynamic property of polymer scaffolds that changes with crosslinker or nanofiller concentration. Here, we report the experimental change in glass transition temperature of gelatin/chitosan scaffolds modified by hydroxyapatite nanoparticles and crosslinker concentration. Our results show synergic effects between nanoparticles and crosslinking, which leads to a non-linear behavior of the glass transition temperature. Furthermore, a theoretical model to predict glass transition is proposed. This model can be used as a mathematical tool for the design of future scaffolds used in bone tissue engineering.